Digital Leadership for Multigenerational Differences: The Path through Creative Climate and Learning Organization toward Innovation Capability - Siti Nur Azizah; Feby Evelyna (International Journal of Community Engagement Payungi, 2025)
This study examines how digital leadership influences innovation capability in Indonesian digital SMEs by incorporating creative climate as a mediator, learning organization as a moderator, and generational differences (Millennials vs. Gen Z) as boundary conditions. Drawing on data from 200 SME employees analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings indicate that digital leadership has no significant direct effect on innovation capability. Instead, creative climate fully mediates the leadership–innovation relationship, while learning organization marginally strengthens this effect. The multi-group analysis reveals that Gen Z employees respond more positively to digital leadership than Millennials, reflecting generational variance in digital adaptability. Theoretically, this research integrates the Componential Theory of Creativity and the Resource-Based View to explain leadership-driven innovation's indirect and conditional mechanisms. Practically, the study highlights that SME leaders must cultivate psychologically safe, creative, and learning-oriented environments that bridge generational differences to sustain innovation in the digital era